(3GdGSJPcGQ dePGgH abgGA GdGeUGQ hYdeGA GdGbWGQ ajeG JVefg GdehWC ef eYGfi GdQCi hGdGKGQs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3Ghd GdehLhO GdGLJeGY efYbO HCf UdGI GdMVQJGeI ZjQ ebUhQI hHGddg GdJhajb s
(3BNQgG (B:s
(3hCLeY GdYdeGA Ydi Cf GdQLGd dGjDege GdfSGA , hGNJdahG ai GeGeI GdfSGA HYVgf dHYV s
(3bWY efg Ghd (B5 (3hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs